The International Politics of Post-Conflict Reconstruction in Guatemala - Short, N. author. aut Link
VII, 188 p.
Keywords: This book looks at the Guatemalan peace process, which was successful in providing a development program to modernize the economy and national infrastructure with the support of international organizations and negotiating parties, analyzing the extent to which peace processes offer opportunity for progressive social transformation.